Comparison of max vo2 levels of elite and deaf footballers - Güzel, Nevin A; Açak, Mahmut; Örer, Gamze Erikoğlu; Savaş, Seyfi; Coşkuner, Zeki (My University, 2012)
The aim of this study is to determine the endurance performance of the players of the hearing handicapped football team and compare it with those professional players in the same age group playing in Turkish 1st and 3rd leagues For this purpose the players of teams in the Turkish first and the third divisions and the Turkish national hearing handicapped football team who won the world championship in 2012 were subjected to shuttle run and their maximum speeds, hearth rates, and maximum oxygen consumption rates (max VO2) were determine. At the end of the study all these three parameters of the hearing handicapped team were found to be lower with a statistically significance extent than the values obtained from the two professional teams(p<0.01) This can be attributed to selection of the players of the handicapped team from a much smaller group of players , the lack of training and competitions and they were forced to work in different jobs due the fact that the economic income they obtained from the sport was not sufficient enough.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Hearing handicapped; Sports; Performance; MaxVO2